2015
DOI: 10.1371/journal.pone.0144336
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Superoxide Dismutase Gene Expression Is Induced by Nanog and Oct4, Essential Pluripotent Stem Cells’ Transcription Factors

Abstract: Pluripotent stem cells possess complex systems that protect them from oxidative stress and ensure genomic stability, vital for their role in development. Even though it has been reported that antioxidant activity diminishes along stem cell differentiation, little is known about the transcriptional regulation of the involved genes. The reported modulation of some of these genes led us to hypothesize that some of them could be regulated by the transcription factors critical for self-renewal and pluripotency in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 34 publications
2
29
1
Order By: Relevance
“…In stem cells, transcription of the SOD2 gene has been shown to be Nanog and Oct4-dependent based on promoter activity assays and RNAi-mediated knockdown of the two pluripotency transcription factors [ 125 ]. Potential Nanog, Oct4, and Sox2 binding sites are located at the 5′ upstream of the SOD2 gene transcription start site, suggesting that these transcription factors may regulate SOD2 in a stem cell-like state [ 125 ].…”
Section: Transcriptional Regulation Of Sod2mentioning
confidence: 99%
See 1 more Smart Citation
“…In stem cells, transcription of the SOD2 gene has been shown to be Nanog and Oct4-dependent based on promoter activity assays and RNAi-mediated knockdown of the two pluripotency transcription factors [ 125 ]. Potential Nanog, Oct4, and Sox2 binding sites are located at the 5′ upstream of the SOD2 gene transcription start site, suggesting that these transcription factors may regulate SOD2 in a stem cell-like state [ 125 ].…”
Section: Transcriptional Regulation Of Sod2mentioning
confidence: 99%
“…In stem cells, transcription of the SOD2 gene has been shown to be Nanog and Oct4-dependent based on promoter activity assays and RNAi-mediated knockdown of the two pluripotency transcription factors [ 125 ]. Potential Nanog, Oct4, and Sox2 binding sites are located at the 5′ upstream of the SOD2 gene transcription start site, suggesting that these transcription factors may regulate SOD2 in a stem cell-like state [ 125 ]. Inhibiting mechanistic Target Of Rapamycin (mTOR) by rapamycin has also been demonstrated to increase SOD2 expression in self-renewing keratinocytes and confers radioprotective effects to these cells [ 126 ], as previously described for hematopoietic progenitor cells [ 127 ].…”
Section: Transcriptional Regulation Of Sod2mentioning
confidence: 99%
“…Based on the growing evidence that antioxidant defense system is modulated when pluripotent stem cells are induced to differentiate, and that glutathione reductase is an important enzyme involved in the cellular response to oxidative stress, we decided to study Gsr gene modulation. In a previous work, we have in silico analyzed the upstream region of the coding sequence of diverse genes involved in antioxidant system, including Gsr and found the presence of multiple predicted binding sites for the transcription factors Oct4 and Nanog in a 5 kbp region upstream the transcription start site of this gene [16]. In this work, we first studied Gsr gene modulation in undifferentiated ESCs and along differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the reported modulation of this system and its importance in securing genomic stability and cellular functions, we hypothesized that some of the antioxidant genes are regulated by the transcription factors fundamental for pluripotency, such as Oct4, Sox2 and Nanog. We have previously found that both sod1 and sod2 genes, that encode for superoxide dismutases, are induced by the pluripotency transcription factors, which are essential for ESCs’ self-renewal and pluripotency [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from our laboratory and others had elucidated the role of SOD2 in maintaining stem cell pluripotency ( Sheshadri et al., 2015 ; Solari et al., 2015 ). Following this observation, we expected that its inhibition would enhance tri-lineage differentiation of mESCs.…”
Section: Discussionmentioning
confidence: 99%